KEARIFAN LOKAL PROSESI PERNIKAHAN DALAM KEBUDAYAAN DESA PUSAR KECAMATAN BATURAJA KABUPATEN OGAN KOMERING ULU - Afriany, Deany (Restorica: Jurnal Ilmiah Ilmu Administrasi Negara dan Ilmu Komunikasi, 2024)
The wedding procession ceremony in the culture of the Navel village is one of the cultural products. Currently, the ceremony is still taking place in the village and is carried out by the people of West Baturaja District in the village of Pusar as one of the socio-cultural aspects. This study aims to (1) describe the wedding ceremony of the village of Pusar and, (2) analyze the local wisdom contained in the wedding ceremony of the village of Pusar. This study uses a qualitative descriptive method. With the research subject, namely OKU Regency in the village of Navel. The problem of this study is the symbolic meaning in the wedding procession with the sacrifice, the slaughter of black goats in the village of Pusar, West Baturaja sub-district. From the results of the study, it can be concluded that the culture of marriage processions with sacrifices, the slaughter of scapegoats was started and created from an idea, an idea that is meaningful and has its own meaning for the people of the Baturaja sub-district, especially in Pusar Village.